P6 Comparison of children testing negative and positive for Ebola virus disease in Ebola holding units, Sierra Leone. (27th April 2016) - Fitzgerald, FC; Wing, K; Naveed, A; Gbessay, M; Ross, JCG; Checchi, F; Youkee, D; Jalloh, MB; Baion, DE; Mustapha, A; Jah, H; Lako, S; et al.
Abstract : Background: The West African Ebola virus disease (EVD) outbreak decimated fragile health systems. The paediatric case definition of EVD is broad, and the symptoms non-specific meaning many children are admitted to Ebola Holding Units (EHUs) as suspect cases who subsequently test negative. Little is known about the characteristics or outcome of these children and caregivers, or their risk of nosocomial EVD infection. Aim: To compare features at presentation in children testing negative and positive for EVD To describe outcomes of children admitted to EHUs who test negative for EVD Method: All children admitted to 11 EHUs in the Western Area, Sierra Leone from 8/14–3/15 aged <12 years were eligible. Retrospective data were collected from site admission books, case investigation forms and clinical records, cross-referenced with district-wide laboratory results, burial records, child protection records and staff interviews in the absence of documentation. Follow-up telephone calls were made to guardians post-discharge. Results: 1059 children were admitted, 309 (29%) testing positive and 750 (71%) negative for EVD, with outcomes available for 91% and 99% respectively. Children testing negative were younger (Median 3 years IQR 1–7 years, versus 4 years, IQR 1.25–8 years, crude OR for each additional year 1.16, 95% CI 1.13–1.21) with a lower case fatality rate (12% vs. 58%, p < 0.001). In crude analysis, features at presentation associated with positive status were history of EVD contact (OR 13.4, 95% CI 9.1–19.6), conjunctivitis (OR 3.29, 95% CI 2.27–4.77), abdominal, joint and muscle pain. Difficulty breathing and skin rash were negative predictors (OR 0.37 and 0.26, 95% CI 0.24–0.57 and 0.13–0.51). Adjusted analysis of features related to EVD positive status is ongoing. 160 guardians admitted to care for children who subsequently tested negative were contacted post discharge. None of the caregivers nor the children contacted were readmitted with EVD (sensitivity analysis ongoing). Conclusion: Clinically distinguishing between children with and without EVD at admission is extremely challenging. There is urgent need for evaluation of sensitive and specific point of care tests for EVD in children. Furthermore, in a spacious and well designed Red Zone alongside handwashing advice, the risks of nosocomial transmission of EVD can be low to caregivers admitted with children who test negative.